Financial Performance Analysis Using Vertical-Horizontal Method at PT. Telekomunikasi Indonesia (Persero) Tbk (Period 2018-2020) - Melly Ratnah Dyah; Musa, Muh. Ichwan; Nurman, Nurman (Economos : Jurnal Ekonomi dan Bisnis, 2023)
Financial performance describes the financial condition of a company in a certain period. This study aims to determine and analyze the financial performance of PT Telekomunikasi Indonesia (Persero) Tbk using financial statement analysis using the vertical-horizontal method. The population in this study is the financial statements of PT Telekomunikasi Indonesia (Persero) Tbk for the 2018-2020 period. The sample used in this study is the financial statements of PT Telekomunikasi Indonesia (Persero) Tbk for the 2018-2020 period. Financial performance of PT. The results of research using the vertical method show that the financial performance of PT Telekomunikasi Indonesia (Persero) Tbk is optimal. This can be seen from total assets that are greater than total liabilities. This indicates that the company is able to fulfill its obligations with the assets owned by the company. The results of research using the horizontal method show that the financial performance of PT Telekomunikasi Indonesia (Persero) Tbk is optimal. Judging from the balance sheet index and income statement, it is optimal, while the cash flow statement shows that it is not optimal.